3D dubins net-recovery path planning for fixed wing UAV - Shi, Hanyi; Lu, Yafei; Hou, Zhongxi; Huang, Shan (Chinese Control and Decision Conference, 2018)
Dubins is a well-known path-planning algorithm for planning the minimum-distance path between two configurations subjects. In this paper, basic Three-Dimension-Dubins (3D Dubins) is used to generate the unmanned aerial vehicle(UAV) net-recovery path for the first time. Following the path, the UAV can bump the net smoothly, fast and precisely. Considering the mobility of the UAV, as well as the safety and efficiency of net recovery, a new net recovery path generation method with 3D Dubins is proposed. Simulation examples with various height differences are carried out to demonstrate the applicability and performance of the improved algorithm. The simulation results prove that the new method is more adaptive to the mobility of UAV and avoids the continuous and long-term turning effectively. It is also promising to be applied in the planning of the guidance path for small fixed-wing UAV net recovery.